IDENTIFICATION OF FACTORS CAUSING CONVICTS OF CHILD PROTECTION CASES IN EFFORTS TO FULFILL DEVELOPMENT RIGHT AT CLASS IIB TEMANGGUNG DETENTION CENTER - Kurniawan, Stevanus Dwi; Biafri, Vivi Silviani (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study seeks to identify factors leading prisoners to commit child protection crimes and evaluate the effectiveness of the inmate development program at the detention center. Utilizing a qualitative approach, data were collected through interviews, observation, and documentation. It identifies three factors influencing behavioral changes: predisposing, enabling, and reinforcing factors. The findings indicate that insufficient knowledge of consequences, a negative social environment, and inadequate family support significantly contribute to these crimes. To address these issues, the study recommends the “Inmate Rehabilitation and Counseling” program, aimed at enhancing legal awareness among inmates, their families, and society while creating a supportive environment. The program includes individual and group guidance along with social skills training to improve the overall quality of life for inmates. Keywords: Prisoners; Casual Factors; Rehabilitation, Counseling